MathOverflow will be down for maintenance for approximately 3 hours, starting Monday evening (06/24/2013) at approximately 9:00 PM Eastern time (UTC-4).

3 added 139 characters in body

I wish to add a remark to Noam D. Elkies' beautiful answer. From the integral representation for $f$, putting $e^{-t}=s$ in the integral, $$f(-x)=1-x\int_0^\infty e^{-xte^{-t}} e^{-t}dt = 1-x\int_0^1 s^{sx}ds\ ,$$ so that, for $x\to \infty$, $f(-x)=o(1)$ is equivalent to $$\int_0^1 xu(s)^xds=1+o(1)\ ,$$ where $u\in C([0,1])$ is the function $u(s):=s^s$. As a matter of fact, since $0\le u(s)\le 1$ for all $s$ and $u(s)=1$ only for $s=0$ or $s=1$, it turns out that the limit only depends on $u'(0)$ and $u'(1)$.

Since $u'(1)=1$, for any $\lambda < 1 < \mu$ there exists a $b < 1$ such that for all $s\in [b,1]$ there holds $$1+\mu(s-1) \le u(s)\le 1+\lambda(s-1)\ ,$$ so that $$x\big(1+\mu(s-1)\big)^x \le xu(s)^x\le x\big(1+\lambda(s-1)\big)^x\ .$$ Similarly, since $u'(0)=-\infty$, for any $\nu > 0$ there exists a $a > 0$ such that for all $s\in [0,a]$ $$u(s)\le1-\nu s\ ,$$ so $$xu(s)^x\le x\big( 1-\nu s\big) ^ x \ .$$

Moreover, since on any interval $[a,b]\subset\subset(0,1)$ the function $u$ is bounded away from $1$, it is clear that $\int_a^b xu(s)^xds=o(1)$ by uniform convergence to $0$.

Integrating over $s\in [ 0,1]$the inequalities above plainly give, and recalling that $\lambda < 1 < \mu$ and $\nu > 0$ were arbitrary, the inequalities above plainly give

$$\int_0^1 xu(s)^xds=\int_0^a x u(s)^xds+\int_a^b xu(s)^xds+\int_b^1 xu(s)^xds=1+o(1) \ ,$$ for $x\to \infty$.

2 added 1 characters in body

I wish to add a remark to Noam D. Elkies' beautiful answer. From the integral representation for $f$, putting $e^{-t}=s$ in the integral, $$f(-x)=1-x\int_0^\infty e^{-xte^{-t}} e^{-t}dt = 1-x\int_0^1 s^{sx}ds\ ,$$ so that, for $x\to \infty$, $f(-x)=o(1)$ is equivalent to $$\int_0^1 xu(s)^xds=1+o(1)$$ (as $x\to xu(s)^xds=1+o(1)\ infty$), ,$$where u\in C([0,1]) is the function u(s):=s^s. As a matter of fact, since 0\le u(s)\le 1 for all s and u(s)=1 only for s=0 or s=1, it turns out that the limit only depends on u'(0) and u'(1). Since u'(1)=1, for any \lambda < 1 < \mu there exists a b < 1 such that for all s\in [b,1] there holds$$1+\lambda(s-1) $1+\mu(s-1) \le u(s)\le 1+\mu(s-1)1+\lambda(s-1)\ .$$Similarly, since u'(0)=-\infty, for any \nu > 0 there exists a a < > 0 such that for all s\in [0,\delta] 0,a]$$u(s)\le1-\nu s\ .$$Moreover, since on any interval [a,b]\subset\subset(0,1) the function u is bounded away from 1, it is clear that \int_a^b xu(s)^xds=o(1) by uniform convergence to 0. Integrating over s\in [ 0,1] the inequalities above plainly give, recalling that \lambda < 1 < \mu and \nu > 0 were arbitrary,$$\int_0^1 xu(s)^xds=\int_0^a x u(s)^xds+\int_a^b xu(s)^xds+\int_b^1 xu(s)^xds=1+o(1) \ ,$$for x\to \infty. 1 I wish to add a remark to Noam D. Elkies' beautiful answer. From the integral representation for f, putting e^{-t}=s in the integral,$$f(-x)=1-x\int_0^\infty e^{-xte^{-t}} e^{-t}dt = 1-x\int_0^1 s^{sx}ds\ ,$$so that f(-x)=o(1) is equivalent to$$\int_0^1 xu(s)^xds=1+o(1)$$(as x\to \infty), where u\in C([0,1]) is the function u(s):=s^s. As a matter of fact, since 0\le u(s)\le 1 for all s and u(s)=1 only for s=0 or s=1, it turns out that the limit only depends on u'(0) and u'(1). Since u'(1)=1, for any \lambda < 1 < \mu there exists a b < 1 such that for all s\in [b,1] there holds$$1+\lambda(s-1) \le u(s)\le 1+\mu(s-1)\ .$$Similarly, since u'(0)=-\infty, for any \nu > 0 there exists a a < 0 such that for all s\in [0,\delta]$$u(s)\le1-\nu s\ .$$Moreover, since on any interval [a,b]\subset\subset(0,1) the function u is bounded away from 1, it is clear that \int_a^b xu(s)^xds=o(1) by uniform convergence to 0. Integrating over s\in 0,1] the inequalities above plainly give, recalling that \lambda < 1 < \mu and \nu > 0 were arbitrary,$$\int_0^1 xu(s)^xds=\int_0^a x u(s)^xds+\int_a^b xu(s)^xds+\int_b^1 xu(s)^xds=1+o(1) \ ,$$for$x\to \infty\$.